The evolution of capitalism and the concept of a natural economic order - Bogusław Fiedor (Ekonomista, 2023)
This paper sets out to prove that the concept of capitalism, perceived as a natural economic system, remains a useful heuristic fiction despite the harsh criticism levelled at it over the past half-century. Capitalism is initially depicted from the neoclassical perspective of methodological monism. The next section outlines a methodological position known as the Variety of Capitalism Approach (Hall and Soskice). The author understands this to be something of an extension of the concept of a natural economic system. The North, Wallis and Weingast hypothesis, which highlights the significance of a system of violence in the evolution of capitalism, is cited. The paper is essentially the author’s reconstruction and extension of that hypothesis from the standpoint of new institutional economics. This is the perspective from which the impact of the quality of the sphere of institutional governance (North) on the scope and composition of the distributive and growth-supporting functions of the modern state are examined. The final section emphasizes that the quality of institutions is decisive in determining the direction of evolution of capitalism.